Significant and Conflicting Correlation of IL-9 With Prevotella and Bacteroides in Human Colorectal Cancer - Niccolai, Elena; Russo, Edda; Baldi, Simone; Ricci, Federica; Nannini, Giulia; Pedone, Matteo; Stingo, Francesco Claudio; Taddei, Antonio; Ringressi, Maria Novella; Bechi, Paolo; Mengoni, Alessio; Fani, Renato; et al. (Frontiers in Immunology, 2021)
Background and aim: Gut microbiota (GM) can support colorectal cancer (CRC) progression by modulating immune responses through the production of both immunostimulatory and/or immunosuppressive cytokines. The role of IL-9 is paradigmatic because it can either promote tumor progression in hematological malignancies or inhibit tumorigenesis in solid cancers. Therefore, we have investigated microbiota-immunity axis in healthy and tumor mucosa, focusing on the correlation between cytokines’ profile and GM signature. Methods: In this observational study, we collected tumor (CRC) and healthy (CRC-S) mucosa samples from 45 CRC patients, undergoing surgery in 2018 at the Careggi University Hospital (Florence, Italy). Firstly, we have characterized the Tissue Infiltrating Lymphocytes (TIL)’s subset profile and the GM composition. Subsequently, we have evaluated the CRC and CRC-S molecular inflammatory response and we have correlated this profile with GM composition, using the Dirichlet Multinomial Regression. Results: CRC samples displayed higher percentages of Th17, Th2 and Tregs. Moreover, CRC tissues showed significantly higher levels of MIP-1α, IL-1α, IL-1β, IL-2, IP-10, IL-6, IL-8, IL-17A, IFN-γ, TNF-α, MCP-1, P-selectin and IL-9. Compared to CRC-S, CRC samples also showed significantly higher levels of the following genera: Fusobacteria, Proteobacteria, Fusobacterium, Ruminococcus2 and Ruminococcus. Finally, the abundance of Prevotella spp. in CRC samples resulted negatively correlated with IL-17A and positively with IL-9. On the contrary, Bacteroides spp. presence resulted negatively correlated with IL-9. Conclusions: Our data consolidate the antitumor immunity impairment and the presence of a distinct microbiota profile in tumor microenvironment compared to the healthy mucosa counterpart. Relating the CRC cytokine profile with the GM composition, we confirm the presence of a bidirectional crosstalk between the immune response and the host’s commensal microorganisms. Indeed, we have documented, for the first time that Prevotella spp. and Bacteroides spp. are respectively positively and negatively correlated with the IL-9, whose role in CRC development is still under debate.